Experimental study on heat transfer of upright pipes in cold regions. (5th May 2017) - Han, Fenglei; Chen, Lin; Yu, Wenbing; Liu, Weibo; Yi, Xin
Highlights: A new technique for cooling permafrost embankment is presented. Laboratory experiment is conducted to investigate the heat transfer characteristic. The up-right pipe can cool the surrounding soil. Abstract: Laboratory experiments are conducted to investigate the heat transfer characteristics of upright pipes under periodic ambient temperatures. The results provide evidence to support the use of upright pipes in permafrost engineering. This paper presents two models with different inlet pipe diameters. The results indicate that the mean periodic temperatures at the bottom of the pipe and soil decrease with increasing freeze-thaw cycles and ultimately remain in a frozen state. Natural convection is the dominant mode of conducting heat exchange between the upright pipe and air. The inlet diameter greatly affects both the cold energy accumulation at the pipe bottom and the cooling efficiency. Furthermore, the lateral thermal disturbance distance of the upright pipe is approximately more than one fold of the inlet diameter. Therefore, the upright pipe enhances the cooling effect to the surrounding soil and is recommended for the cooling of permafrost foundations.